New species of Leptohyphidae (Ephemeroptera) from northeastern Brazil - Lima, Lucas R. C.; Salles, Frederico F.; Pinheiro, Ulisses Dos S. (Zootaxa, 2011)
Two new species of Leptohyphidae are described based on nymphs and adults: Traverhyphes (Traverhyphes) frevo sp. nov. and Tricorythopsis spongicola sp. nov. Traverhyphes (T.) frevo can be distinguished from other species, among other characteristics, by the presence of curved penile spines inserted laterally, and posterolateral projections of styliger plate very short and pointed distally in lateral view. Tricorythopsis spongicola can be distinguished from the others species, mainly by the presence of spine-like lateral projections present on apical part of penes in the male imago, and by the tarsal claws with four to five marginal denticles, and two rows of 2 + 3 submarginal denticles with apical setae in the nymphs.